Distribution and abundance of stomatopods (Crustacea: Haplocarida) in Southern Sinaloa, Mexico - Hendrickx, M. E. (1984)
Samples of benthic macrofauna were collected by trawl and grab-dredge during seasonal cruises along three transects on the coastal shelf of Southern Sinaloa. Mexico (SIPCO cruises) from 27 to 117 m and included 6 species of stomatopods. Squilla biformis Bigelow and S. parva Bigelow were the most abundant species. All species were found in shallow water (31-75 m) except Squilla biformis which occurred mostly below 100 m, where dissolved oxygen concentration was lower than 0.6 m/L. Other species found are: Squilla panamensis Bigelow, S. hancocki Schmitt, Meiosquilla swetti (Schmitt) and Eurysquilla veleronis (Schmitt).